Respuestas

¡La mejor respuesta!
2013-08-21T20:33:15+02:00

1..(x+y)(n+1)-3(n+1)= (n + 1)[(x + y) - 3] = (n + 1).(x + y - 3)     FACTOR COMUN
2..((a+1) (a-1)-2 (a-1)= (a - 1)[(a + 1) - 2)] = (a - 1)(a - 1)            FACTOR COMÚN
3..(a(+a+b)-b(a+b)= (a + b)(a - b)                                            FACTOR COMÚN
4..(2x+3)(3-r)-(2x-5)(3-r)= (3 - r)[(2x + 3) - (2x - 5)] = (3 - r) [2x + 3 - 2x + 5]
                                                                        = 8.(3 - r)      FACTOR COMÚN